2008
DOI: 10.1053/j.ajkd.2007.11.010
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Risk Factors for Incident Albuminuria in Diabetic American Indians: The Strong Heart Study

Abstract: Background-There have been no studies that employ longitudinal data with more than two measurements and use methods of longitudinal data analysis to identify risk factors for incident albuminuria over time more effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 40 publications
1
19
2
Order By: Relevance
“…This may reflect confounding by indication, given the use of these drugs to control albuminuria or hypertension, especially among patients with diabetes [24]. In contrast to other studies [25], a high HDL was found to be associated with a lower risk for albuminuria in our sample, which included those with and without diabetes.…”
Section: Discussioncontrasting
confidence: 69%
“…This may reflect confounding by indication, given the use of these drugs to control albuminuria or hypertension, especially among patients with diabetes [24]. In contrast to other studies [25], a high HDL was found to be associated with a lower risk for albuminuria in our sample, which included those with and without diabetes.…”
Section: Discussioncontrasting
confidence: 69%
“…These results suggest that high-normal DBP alone or in combination with metabolic disorders could initiate glomerular damage, leading to future microalbuminuria. Our data are consistent with the previous studies showing that baseline level of urinary albumin excretion is a strong predictor for future microalbuminuria in hypertensive, diabetic, and general population [11,18,19]. The mechanism of the link with slightly increased baseline urinary albumin excretion and incidence of microalbuminuria has never been clarified.…”
Section: Discussionsupporting
confidence: 89%
“…We found an association between mean follow-up HDL-C level and new-onset microalbuminuria. Similarly, Xu et al 29 reported low HDL-C level to be a predictor of incidental albuminuria in a longitudinal study.…”
Section: Commentmentioning
confidence: 83%